A plastid-localized glycogen synthase kinase 3 modulates stress tolerance and carbohydrate metabolism - Kempa, Stefan (Blackwell Publishing Ltd, 2007)
Glycogen synthase kinase 3 (GSK-3) was originally identified as a regulator of glycogen synthesis in mammals. Like starch in plants, glycogen is a polymer of glucose, and serves as an energy and carbon store. Starch is the main carbohydrate store in plants. Regulation of starch metabolism, in particular in response to environmental cues, is of primary importance for carbon and energy flow in plants but is still obscure. Here, we provide evidence that MsK4, a novel Medicago sativa GSK-3-like kinase, connects stress signalling with carbon metabolism. MsK4 was found to be a plastid-localized protein kinase that is associated with starch granules. High-salt stress rapidly induced the in vivo kinase activity of MsK4. Metabolic profiling of MsK4 over-expressor lines revealed changes in sugar metabolism, including increased amounts of maltose, the main degradation product of starch in leaves. Plants over-expressing MsK4 showed improved tolerance to salt stress. Moreover, under high-salinity conditions, MsK4-over-expressing plants accumulated significantly more starch and showed modified carbohydrate content compared with wild-type plants. Overall, these data indicate that MsK4 is an important regulator that adjusts carbohydrate metabolism to environmental stress.